2015
DOI: 10.3109/10837450.2015.1026605
|View full text |Cite
|
Sign up to set email alerts
|

A novel nanogel formulation of methotrexate for topical treatment of psoriasis: optimization, in vitro and in vivo evaluation

Abstract: The developed MTX-NLC gel formulation can be a promising alternative to existing MTX formulation in treating psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 34 publications
(39 reference statements)
3
50
0
Order By: Relevance
“…In the thermograms of the knitted textile substrates functionalized with NLCs (blue thermogram) either by exhaustion or by impregnation, there are two endothermic transitions between 51 and 64 °C which correspond to the endothermic transition of the cotton that occurred in the control, and to the endothermic transition of the solid lipid used (Precirol® ATO5). The endothermic transition of the solid lipid is in agreement with the obtained by Avasatthi et al (63.8 °C) [48]. Wang et al [49] demonstrated that, when Precirol® ATO5 is incorporated into NLC dispersions, No thermal transition related to the presence of omega-3 was observed, which was already expected since this compound is liquid at room temperature.…”
Section: Functionalization Of Textile Substratessupporting
confidence: 89%
“…In the thermograms of the knitted textile substrates functionalized with NLCs (blue thermogram) either by exhaustion or by impregnation, there are two endothermic transitions between 51 and 64 °C which correspond to the endothermic transition of the cotton that occurred in the control, and to the endothermic transition of the solid lipid used (Precirol® ATO5). The endothermic transition of the solid lipid is in agreement with the obtained by Avasatthi et al (63.8 °C) [48]. Wang et al [49] demonstrated that, when Precirol® ATO5 is incorporated into NLC dispersions, No thermal transition related to the presence of omega-3 was observed, which was already expected since this compound is liquid at room temperature.…”
Section: Functionalization Of Textile Substratessupporting
confidence: 89%
“…More recently, Avasatthi et al used 278-nm nanostructured lipid carriers to deliver methotrexate in a mouse model. They observed slower, more prolonged release of the drug, and they revealed that the drug nanocarrier system decreases the psoriatic area and severity index, compared to drug alone in an imiquimod-induced mouse model of psoriasis [ 114 ]. Cyclosporin A is another oral drug used to inhibit T cells and induce immunosuppression in severe cases of both atopic dermatitis and psoriasis.…”
Section: Transdermal Nanocarriers For the Treatment Of Skin Diseasmentioning
confidence: 99%
“…[46] PROPERTIES OF NANOGELS to MTX gel, and the PASI score is also get reduced in MTX-NLC formulation. [47] Like this way, Divya et al focused on the development of an effective topical nanogel formulation of two anti-psoriatic drugs; Act and aloe-emodin using natural polymer chitin. They had done with ex vivo and in vivo studies in which ex vivo skin permeation studies using porcine skin confirmed the higher deposition of the systems at epidermal and dermal layers, which was confirmed further by fluorescent imaging.…”
Section: Novel and Advance Approaches For Psoriasis Nanogelmentioning
confidence: 99%